Atopic dermatitis: allergic dermatitis or neuroimmune dermatitis? - Neide Kalil Gaspar; Márcia Kalil Aidé (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Advances in knowledge of neurocellulars relations have provided new directions in the understanding and treatment of numerous conditions, including atopic dermatitis. It is known that emotional, physical, chemical or biological stimuli can generate more accentuated responses in atopic patients than in non-atopic individuals; however, the complex network of control covered by these influences, especially by neuropeptides and neurotrophins, and their genetic relations, still keep secrets to be revealed. Itching and airway hyperresponsiveness, the main aspects of atopy, are associated with disruption of the neurosensory network activity. Increased epidermal innervation and production of neurotrophins, neuropeptides, cytokines and proteases, in addition to their relations with the sensory receptors in an epidermis with poor lipid mantle, are the aspects currently covered for understanding atopic dermatitis.